Detection of lung transplant rejection in a rat model using hyperpolarized [1‐13C] pyruvate‐based metabolic imaging. (21st May 2019) - Siddiqui, Sarmad; Habertheuer, Andreas; Xin, Yi; Pourfathi, Mehrdad; Tao, Jian‐Qin; Hamedani, Hooman; Kadlecek, Stephen; Duncan, Ian; Vallabhajosyula, Prashanth; Naji, Ali; Chatterjee, Shampa; Rizi, Rahim
Abstract : The current standard for noninvasive imaging of acute rejection consists of X‐ray/CT, which derive their contrast from changes in ventilation, inflammation and edema, as well as remodeling during rejection. We propose the use of hyperpolarized [1‐ 13 C] pyruvate MRI—which provides real‐time metabolic assessment of tissue—as an early biomarker for tissue rejection. In this preliminary study, we used μCT‐derived parameters and HP 13 C MR‐derived biomarkers to predict rejection in an orthotopic left lung transplant model in both allogeneic and syngeneic rats. On day 3, the normalized lung density—a parameter that accounts for both lung volume (mL) and density (HU)—was −0.335 (CI: ‐0.598, −0.073) and − 0.473 (CI: ‐0.726, −0.220) for the allograft and isograft, respectively (not significant, 0.40). The lactate‐to‐pyruvate ratios—derived from the HP 13 C MRI—for the allograft and isograft were 0.200 (CI: 0.161, 0.240) and 0.114 (CI: 0.074, 0.153), respectively (significant, 0.020). Both techniques showed tissue rejection on day 7. A separate sub‐study revealed CD8+ cells as the primary source of the lactate‐to‐pyruvate signal. Our study suggests that hyperpolarized (HP) [1‐ 13 C] pyruvate MRI is a promising early biomarker for tissue rejection that provides metabolic assessment in real time based on changes in cellularity and metabolism of lung tissue and the infiltrating inflammatory cells, and may be able to predict tissue rejection earlier than X‐ray/CT. Abstract : HP [1‐ 13 C] pyruvate MR‐derived biomarkers and μCT‐derived parameters were used to predict rejection in an orthotopic left lung transplant model in allogeneic and syngeneic rats. As seen above, the distribution of HP [1‐ 13 C] lactate labeling after injection of HP [1‐ 13 C] pyruvate can distinguish between nonrejected (syngeneic) and rejected (allogeneic) transplanted lungs as early as three days post‐transplantation based on the real‐time metabolic assessment of changes in cellularity and metabolism of lung tissue and the infiltrating inflammatory cells.